Heart-Derived Stem Cells in Miniature Swine with Coronary Microembolization: Novel Ischemic Cardiomyopathy Model to Assess the Efficacy of Cell-Based Therapy - Gen Suzuki; Rebeccah F. Young; Merced M. Leiker; Takayuki Suzuki (Stem Cells International)
A major problem in translating stem cell therapeutics is the difficulty of producing stable, long-term severe left ventricular (LV) dysfunction in a large animal model. For that purpose, extensive infarction was created in sinclair miniswine by injecting microspheres (1.5 × 106 microspheres, 45 μm diameter) in LAD. At 2 months after embolization, animals (n=11) were randomized to receive allogeneic cardiosphere-derived cells derived from atrium (CDCs: 20 × 106, n=5) or saline (untreated, n=6). Four weeks after therapy myocardial function, myocyte proliferation (Ki67), mitosis (phosphor-Histone H3; pHH3), apoptosis, infarct size (TTC), myocyte nuclear density, and cell size were evaluated. CDCs injected into infarcted and remodeled remote myocardium (global infusion) increased regional function and global function contrasting no change in untreated animals. CDCs reduced infarct volume and stimulated Ki67 and pHH3 positive myocytes in infarct and remote regions. As a result, myocyte number (nuclear density) increased and myocyte cell diameter decreased in both infarct and remote regions. Coronary microembolization produces stable long-term ischemic cardiomyopathy. Global infusion of CDCs stimulates myocyte regeneration and improves left ventricular ejection fraction. Thus, global infusion of CDCs could become a new therapy to reverse LV dysfunction in patients with asymptomatic heart failure.